PERSEPSI PETANI TERHADAP PENGGUNAAN PUPUK KOMPOS PADA USAHATANI PADI DI KELOMPOK TANI HARAPAN DESA POGALAN KECAMATAN POGALAN KABUPATEN TRENGGALEK - Naudya Wulan Aprilianti; Sutoyo Sutoyo; Eny Wahyuning Purwanti (University of Jember, 2020)
Compost fertilizer is fertilizer that comes from the remains of organic matter through a decomposition process with the aim of improving soil structure. This research aimed to determine farmers' perceptions of the use of compost on rice farming, the influence of internal factors and external factors on the perceptions of farmers in using compost on rice farming, and the design of extension and use of compost fertilizer on rice farming to determine the perceptions of farmers on the use of compost fertilizer on rice farming. The research method used is the survey method. The sampling method uses purposive sampling method. The results of this study showed that the highest perception received was 57,1% based on making compost, the age and experience of rice farming do not affect farmers' perceptions, and the design of counseling uses the material for making also using compost on rice farming; the methods used are visual, audio visual, lecture, and discussion; the media used is film.